Optimization of Physics Learning on Uniform Linear Motion (GLB) and Uniformly Accelerated Linear Motion (GLBB) Through Interactive Virtual Practicum Simulation Based on Phet - Bumi, Philosofi Setia; Umam, Rofiqul; Saregar, Antomi (Islamic Journal of Integrated Science Education (IJISE), 2025)
Limited laboratory facilities remain a challenge in physics learning, especially for topics such as Uniform Linear Motion (GLB) and Uniformly Accelerated Linear Motion (GLBB). To address this issue, a Classroom Action Research (CAR) was conducted at SMAN 8 Yogyakarta using interactive virtual experiments based on PhET simulations. The study was carried out in two cycles involving planning, implementation, observation, and reflection. Data were collected through observation, interviews, documentation, and student worksheets (LKPD) assessment. Results showed that PhET simulations significantly improved student engagement and conceptual understanding. In class X-E1, 71.9% of students achieved a perfect score (100), and the rest scored above 62.5. Similar outcomes were found in classes X-E2 to X-E4, with most students achieving high scores. PhET proved to support contextual and interactive learning, enhancing student participation, concept mastery, and scientific process skills, while also providing meaningful learning experiences without relying on physical lab equipment.